2011
DOI: 10.1002/jcc.21964
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the reaction CX3 + SiH(CH3)3 (X = H, F)

Abstract: Theoretical investigations are carried out on the multiple-channel reactions, CH(3) + SiH(CH(3))(3) → products and CF(3) + SiH(CH(3))(3) → products. The minimum energy paths (MEP) are calculated at the MP2/6-311 + G(d,p) level, and energetic information is further refined by the MC-QCISD (single point) method. The rate constants for major reaction channels are calculated by the canonical variational transition state theory (CVT) with small-curvature tunneling (SCT) correction over the temperature range 200-150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…Since Si has significantly smaller atomic radius than Mo, the lattice parameter of Mo decreases by alloying with Si. The formation of substitutional solid solution of Si in Mo has been reported in the literature [37,43,50]. According to mentioned discussions, it can be concluded that Mo(Si,B) solid solution can be formed after 10 h of milling.…”
Section: Structural Evolutionmentioning
confidence: 83%
See 1 more Smart Citation
“…Since Si has significantly smaller atomic radius than Mo, the lattice parameter of Mo decreases by alloying with Si. The formation of substitutional solid solution of Si in Mo has been reported in the literature [37,43,50]. According to mentioned discussions, it can be concluded that Mo(Si,B) solid solution can be formed after 10 h of milling.…”
Section: Structural Evolutionmentioning
confidence: 83%
“…The Vickers microhardness at the polished cross-section of powders was measured with a microhardness tester at a load of 100 g and dwell time of 10 s. Ten Vickers indentation marks were performed on each sample. mechanical alloying of Mo-Si which can be attributed to the intimate mixing of the two elements, the strong absorption of Mo and dissolution of Si into Mo lattice during mechanical alloying [41][42][43].…”
Section: Methodsmentioning
confidence: 99%
“…6 and are listed in Table 1. The degree of crystallinity X c of the UHMWPE composites compared to pure UHMWPE can be calculated by using the relation [29]. According to Fig.…”
Section: Thermo-mechanical Properties Of B 4 C-uhmwpe Compositesmentioning
confidence: 99%
“…Ball milling has been used for preparations of either various nanoparticles or surface coated nanocomposites [17][18][19][20][21][22][23][24][25][26]. Theoretical evaluations using the energy transfer between the balls and materials have been also reported [27][28][29][30]. The present investigation is focused on pulverization of micro-sized B 4 C powder as well as PVA coating on the B 4 C particles.…”
Section: Introductionmentioning
confidence: 95%
“…B and Si peaks cannot be detected in XRD pattern at this stage. The intimate mixing of elements and strong absorption of Mo are the main reasons for complete disappearance of Si and B peaks at early stages of MA [56][57][58][59][60][61][62].…”
Section: Structural Evolutions During Second Step Of Mechanical Alloyingmentioning
confidence: 99%